AgriTech Toolbox: Using agricultural technologies for enhanced productivity and sustainable food security - International Food Policy Research Institute (Spatial Dev, 2014)
The AgriTech Toolbox enables researchers and policymakers to examine how alternative agricultural practices and technologies can impact farm yields, food prices, natural resource use, hunger, malnutrition, land use and global trade in 2050, when climate change impacts may be severe. As a result, it can inform the right mix of policies and investments needed to tackle the challenges agriculture faces in the coming decades. The AgriTech toolbox models the impacts of 10 technologies on farm yields, food prices, natural resource use, hunger, malnutrition, land use and global trade. The Raw data can be downloaded by clicking on the 'download button' on the top right of the menu bar, both in the crop model and economic model pages.